2015
DOI: 10.1111/adb.12291
|View full text |Cite
|
Sign up to set email alerts
|

The effects of single nucleotide polymorphisms in glutamatergic neurotransmission genes on neural response to alcohol cues and craving

Abstract: The aim of the current study was to determine genotype effects of four single nucleotide polymorphisms (SNPs) in the genes of the N-Methyl-d-aspartate receptor (GRIN1, GRIN2A, GRIN2C) and kainate receptor (GRIK1), which have been previously associated with alcoholism, on behavior, neural cue-reactivity and drinking outcome. Eighty-six abstinent alcohol dependent patients were recruited from an in-patient setting. Neuropsychological tests, genotyping and functional magnetic resonance imaging (fMRI) were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…In a massive genetics study, Schumann et al . 128 reported that genetic variations in GluN2A have the greatest relevance for human alcohol dependence among 10 glutamatergic probe genes, yet increased GluN2B expression and GluN2C in the ACC and dorsolateral PFC during withdrawal can indicate likelihood of alcohol craving and risk for relapse 129, 130 . It appears that the ACC is a distinct site for glutamate plasticity in heavy drinking.…”
Section: Heavy Drinking and Withdrawalmentioning
confidence: 99%
“…In a massive genetics study, Schumann et al . 128 reported that genetic variations in GluN2A have the greatest relevance for human alcohol dependence among 10 glutamatergic probe genes, yet increased GluN2B expression and GluN2C in the ACC and dorsolateral PFC during withdrawal can indicate likelihood of alcohol craving and risk for relapse 129, 130 . It appears that the ACC is a distinct site for glutamate plasticity in heavy drinking.…”
Section: Heavy Drinking and Withdrawalmentioning
confidence: 99%
“…Other clinical studies have shown that memantine reduces intake and cravings in treatment‐seeking AUD patients with co‐morbid depression (Muhonen et al ), although it had no effect in another study of treatment‐seekers (Evans et al ). Nonetheless, a GluN2C single nucleotide polymorphism linked to risk for alcoholism is associated with greater activation of several cortical areas by alcohol cues, and where brain activity is related to both craving and future relapse (Bach et al ). Taken together, these findings suggest that non‐canonical NMDARs can play a significant role in regulating addiction to alcohol, and perhaps other drugs of abuse (Sedaghati et al ), particularly under conditions where there is conflict regarding intake.…”
Section: Non‐canonical Nmdars and Cocaine And Alcohol Addictionmentioning
confidence: 99%
“…Bach et al . ) and indicated cue‐induced activation of the VS only when comparing alcohol dependent patients and healthy controls after small volume correction analyses (e.g. Vollstädt‐Klein et al .…”
Section: Introductionmentioning
confidence: 99%